Play-Based Community Service Program to Develop Early Childhood Motor Skills - Dewi Fitriani; Rani; Arista Arista; Mazeni Binti Ismail (CV Berkah Syahdin Trust, 2026)
Background: Early childhood motor development is a fundamental aspect that supports children’s physical growth, coordination, and readiness for learning. However, limited stimulation through structured and engaging activities often results in suboptimal motor skill development in early childhood education settings, particularly in community-based environments. Aims: This community service program aims to improve early childhood motor skills through the implementation of play-based learning activities that are engaging, participatory, and developmentally appropriate. Methods: This program employed a Participatory Action Research (PAR) approach involving collaboration between lecturers, teachers, and children. The participants consisted of early childhood learners aged 4–6 years in a community-based educational setting. The intervention was conducted through structured play activities such as movement games, outdoor play, and guided physical exercises designed to stimulate gross motor skills. Data were collected through observation and documentation and analyzed descriptively across implementation stages. Results: The implementation of play-based activities showed a significant improvement in children’s motor skills, including balance, coordination, and body movement control. Children demonstrated higher participation, enthusiasm, and confidence during physical activities. In addition, teachers showed increased ability in designing and implementing interactive play-based learning strategies. Conclusion: The play-based community service program effectively enhanced early childhood motor development and strengthened teachers’ pedagogical capacity. The findings indicate that simple, contextual, and engaging play activities can provide meaningful stimulation for children’s physical development and can be sustainably implemented in early childhood education settings.